Effects of Interim Buprenorphine Treatment for opioid use disorder among emerging adults. (1st March 2020) - Peck, Kelly R.; Ochalek, Taylor A.; Badger, Gary J.; Sigmon, Stacey C.
Highlights: Opioid misuse is disproportionately elevated among 18–25 year old emerging adults. Emerging adults may also have worse opioid treatment response than older adults. Emerging adults presented with more past-year IV drug use relative to older adults. Emerging adults exhibited a favorable response to interim buprenorphine treatment. Low-barrier buprenorphine treatment may hold promise for emerging adults. Abstract: Objective: Although opioid maintenance is a first-line approach for treating opioid use disorder (OUD), suboptimal treatment outcomes have been reported among emerging adults (EAs; 18-25 years of age). In this secondary analysis, we compared treatment outcomes between EAs and older adults (OAs; ≥ 26 years of age) receiving low-barrier, technology-assisted Interim Buprenorphine Treatment (IBT) during waitlist delays to comprehensive opioid maintenance treatment. Method: Participants were 35 individuals with OUD who received IBT consisting of 12-weeks of buprenorphine maintenance with bi-monthly clinic visits and technology-assisted monitoring. At monthly follow-up assessments, participants completed staff-observed urinalysis, the Beck Anxiety Inventory (BAI), Beck Depression Inventory (BDI-II), and Addiction Severity Index (ASI). Results: At study intake, EAs ( n = 10) reported greater past-year intravenous drug use and greater employment, legal, and psychiatric severity ( p 's < .05) compared to OAs ( n = 25). Despite these initial differences, there were no significant differences in the percentages of urine specimens testing negative for illicit opioids between EA and OA participants at Study Week 4 (90 % vs. 88 %, p = .99), Week 8 (80 % vs. 76 %, p = .99) or Week 12 (60 % vs. 68 %, p = .71). Relative to their older peers, EAs also demonstrated significantly greater improvements on the BAI, BDI-II, and ASI Employment and Legal subscales ( p 's < .05). Conclusions: Despite presenting with greater past-year intravenous drug use and psychosocial severity relative to OAs, EAs responded favorably to the IBT intervention.